The changing network of financial market linkages: The Asian experience - Biplob Chowdhury; Mardi H. Dungey; Moses Kangogo; Mohammad Abu Sayeed; V. V. Volkov (Asian Development Bank (ADB), 2018)
Recent international financial crises highlight the advantages of understanding the global financial system as a network of economies in which cross-border financial linkages are fundamental to the spread of systemic risk. We investigate the changing network of financial markets for six periods from 1995-2016, constructing a network that captures the concepts of the direction of links between markets, the significance of these links, and their strength. Emphasis is placed on the transition of the networks before and after the Asian financial crisis of 1997-1998 and the global financial crisis of 2008-2009. The analysis demonstrates the increase in interconnectedness during periods of stress and the fall in the number of links in postcrisis periods. At the same time, the results reveal a general deepening of the connections of the Asian market with the rest of the world over the past 2 decades. They also suggest that many of these markets have transitioned from being primarily linked to developed non-Asian markets through key bridge markets (such as Hong Kong, China) to developing stronger direct links with these external markets, highlighting the importance of key geographical nodes in market development.
Keywords: G01; G10; G15; 330; Asian markets; financial crises; network